Genomic analyses of multidrug resistant Pseudomonas aeruginosa PA1 resequenced by single-molecule real-time sequencing. Issue 6 (29th November 2016) - Li, Gang; Shen, Mengyu; Le, Shuai; Tan, Yinling; Li, Ming; Zhao, Xia; Shen, Wei; Yang, Yuhui; Wang, Jing; Zhu, Hongbin; Li, Shu; Rao, Xiancai; et al.
Abstract : As a third-generation sequencing (TGS) method, single-molecule real-time (SMRT) technology provides long read length, and it is well suited for resequencing projects and de novo assembly. In the present study, Pseudomonas aeruginosa PA1 was characterized and resequenced using SMRT technology. PA1 was also subjected to genomic, comparative and pan-genomic analyses. The multidrug resistant strain PA1 possesses a 6, 498, 072 bp genome and a sequence type of ST-782. The genome of PA1 was also visualized, and the results revealed the details of general genome annotations, virulence factors, regulatory proteins (RPs), secretion system proteins, type II toxin–antitoxin (T–A) pairs and genomic islands. Whole genome comparison analysis suggested that PA1 exhibits similarity to other P. aeruginosa strains but differs in terms of horizontal gene transfer (HGT) regions, such as prophages and genomic islands. Phylogenetic analyses based on 16S rRNA sequences demonstrated that PA1 is closely related to PAO1, and P. aeruginosa strains can be divided into two main groups. The pan-genome of P. aeruginosa consists of a core genome of approximately 4, 000 genes and an accessory genome of at least 6, 600 genes. The present study presented a detailed, visualized and comparative analysis of the PA1 genome, to enhance our understanding of this notorious pathogen.